Fungsi Taman Pendidikan Al Qur’an (TPA) Masjid Al Ikhlas dalam penanaman akhlak pada anak di Desa Padaan Kecamatan Grogol Kabupaten Sukoharjo - Afifah Nur Izzah; Hafidz Hafidz (At Turots: Jurnal Pendidikan Islam, 2023)
The purpose of education is to help people reach their full potential. Moral education is an important thing for oneself or in socializing between fellow humans and the environment in Islamic law. The cultivation of moral values needs to be given as early as possible so that it is always embedded in a person. TPA has an important function in growing and producing generations of Muslims who learn and practice Islamic teachings by the Qur'an and Sunnah. The purpose of this study was to find out how the Qur'an Education Park (TPA) contributes to the moral development of the students. In this study, the qualitative approach is combined with descriptive methodology. A method of study known as a qualitative approach describes events that occur today based on the reality of human existence as it is. From the results of interviews, observations, and documentation, there are results that in the Al-Qur'an Al-Ikhlas Education Park, there is a provision for learning about knowledge of Islamic religious teachings (habituation to write hijaiyah letters upright regularly, reading iqro '/ al-Qur'an, memorizing surah juz 30, memorizing selected verses, memorizing hadiths, memorizing daily prayers, good habituation for oneself and among others and so on), and habituation of manners (to the ustazah and between friends).